OPTIMIZING FAMILY COMMUNICATION IN MAINTAINING MENTAL ADOLESCENTHEALTH IN WEST JAVA - Bakti , Iriana; Zubair, Feliza; Sjoraida , Diah Fatma (Yayasan Kreatif Indonesia Emas, 2024)
Effective family communication plays a pivotal role in maintaining adolescent mental health. This study focuses on the significance of optimizing family communication to support the mental well-being of adolescents in West Java, a region rich in cultural diversity and strong family values. The research highlights the importance of democratic communication patterns within families, where every member has the opportunity to speak and be heard. Such communication fosters emotional and psychological development in adolescents, making them more resilient to external pressures from school and peer groups. Despite its importance, effective family communication faces several challenges, including generational gaps, the influence of technology, and a lack of communication skills among parents. The study proposes several strategies to overcome these obstacles. Utilizing local cultural values, such as those found in Sundanese traditions, can enhance family communication. Additionally, schools and communities play critical roles in supporting families through counseling programs and educational workshops. Technology, if used wisely, can also facilitate communication and provide educational resources. Continuous evaluation and monitoring are essential to ensure the effectiveness of these strategies. Surveys, interviews, and direct observations can help assess changes in family communication patterns and their impact on adolescent mental health. Government policies supporting mental health programs and family communication training are crucial. Psychologists and counselors are vital in providing individual and family counseling services, facilitating workshops, and supporting families in managing communication challenges. The findings of this study underscore the need for collaborative efforts among families, schools, communities, and government bodies to create a supportive environment for adolescents. By implementing comprehensive programs and policies that promote effective family communication, it is possible to enhance the mental health of adolescents in West Java. This research provides a strong foundation for developing effective intervention programs tailored to the local context and serves as a reference for further studies in this field.